GRAIN QUALITY OF WINTER WHEAT SOFT AND WAYS TO INCREASE IT - Герман, М. М.; Маренич, М. М. (Scientific Progress & Innovations, 2013)
The analysis has found that nitrogen fertilization on the background of N50P50K50, N75P75K75 and preplant inoculation of seed by growth-stimulating and biologically active substances («Vympel» (120 ml/m) and «Agate-25K» (60 g/t), «Polimiksobakteryn» (150 ml/m ) and «Diazofit» (150 ml/m) help to increase the weight of 1000 grains, nature, protein content and gluten. According to a scientific study found the highest increase in 1000 grain weight, nature, protein content and gluten soft winter wheat in the application of bacterial preparations of «Polimiksobakteryn» and «Diazofit» at a dose of 150 ml/t.